2018
DOI: 10.1089/thy.2017.0414
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism and the Risk of Cardiovascular Disease and All-Cause Mortality: A Meta-Analysis of Prospective Cohort Studies

Abstract: SCH is associated with an increased CVD risk and all-cause mortality, particularly in participants with high CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 61 publications
3
74
0
3
Order By: Relevance
“…C ardiovascular disorders (CVD) are a leading cause of mortality worldwide (1). Whereas traditional cardiovascular risk factors, such as dyslipidemia, hypertension, type 2 diabetes (T2D), and obesity, are well-recognized, observational studies have shown that also overt and subclinical thyroid dysfunction is associated with a higher risk of CVD (2)(3)(4)(5)(6). More recently, even variation in normal range thyroid function has been associated with an increased risk of CVD, including atherosclerotic disease and stroke (7)(8)(9)(10), as well as with serum lipid levels (11), blood pressure (12), T2D risk (13), and obesity (14).…”
Section: Introductionmentioning
confidence: 99%
“…C ardiovascular disorders (CVD) are a leading cause of mortality worldwide (1). Whereas traditional cardiovascular risk factors, such as dyslipidemia, hypertension, type 2 diabetes (T2D), and obesity, are well-recognized, observational studies have shown that also overt and subclinical thyroid dysfunction is associated with a higher risk of CVD (2)(3)(4)(5)(6). More recently, even variation in normal range thyroid function has been associated with an increased risk of CVD, including atherosclerotic disease and stroke (7)(8)(9)(10), as well as with serum lipid levels (11), blood pressure (12), T2D risk (13), and obesity (14).…”
Section: Introductionmentioning
confidence: 99%
“…11 Although the manifestation of subclinical hypothyroidism (SHypo) is often silent and obscure, SHypo is related to an increased risk of fracture, cardiovascular disease and all-cause mortality. 12,13 The prevalence of SHypo is much higher than that of overt hypo-or hyperthyroidism. 14 However, the relationships of thyroid hormones with GA and GA/HbA 1c in euthyroid and SHypo individuals have not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…H ypothyroidism is a common condition (1,2) associated with an increased cardiovascular risk profile (3)(4)(5) and poor quality of life (6,7). The goal of its therapy is the relief of symptoms and restoration of normal thyroid hormone levels by administration of synthetic thyroxine (T4), levothyroxine (LT4), which is then converted in the periph-eral tissues into the hormonally active triiodothyronine (T3) (8).…”
Section: Introductionmentioning
confidence: 99%